2009
DOI: 10.1115/1.3063818
|View full text |Cite
|
Sign up to set email alerts
|

A Voronoi Finite Element Study of Fatigue Life Scatter in Rolling Contacts

Abstract: Microlevel material failure has been recognized as one of the main modes of failure for rolling contact fatigue (RCF) of bearing. Therefore, microlevel features of materials will be of significant importance to RCF investigation. At the microlevel, materials consist of randomly shaped and sized grains, which cannot be properly analyzed using the classical and commercially available finite element method. Hence, in this investigation, a Voronoi finite element method (VFEM) was developed to simulate the microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…To overcome this limitation, a few models, including finite element models, were developed to take into account the micromechanical material behavior in the contact region. A so-called Voronoi finite element method (VFEM) was proposed by Jalalahmadi and Sadeghi [31]. With the implementation of a fatigue life criterion [32], VFEM can be used to study the effect of material micromechanical behavior on rolling contact fatigue.…”
Section: Multiscale Modeling and Simulation Of Rolling Contact Fatiguementioning
confidence: 99%
“…To overcome this limitation, a few models, including finite element models, were developed to take into account the micromechanical material behavior in the contact region. A so-called Voronoi finite element method (VFEM) was proposed by Jalalahmadi and Sadeghi [31]. With the implementation of a fatigue life criterion [32], VFEM can be used to study the effect of material micromechanical behavior on rolling contact fatigue.…”
Section: Multiscale Modeling and Simulation Of Rolling Contact Fatiguementioning
confidence: 99%
“…They used Voronoi tessellations to capture the effect of microstructural randomness of the material in RCF. Jalalahmadi and Sadeghi [37], extended the approach to FEM. They, in particular, studied the effect of inclusions on fatigue crack initiation [1].…”
Section: Introductionmentioning
confidence: 99%
“…At microlevel, materials consist of grains which are random in size and shape. Ito and Fuller [25], Zavattieri and Espinosa [27], and Jalalahmadi and Sadeghi [33] showed that the Voronoi diagram can be used to simulate the topology of the material microstructure. Their reasoning for using the Voronoi diagram was that consider some random nucleation points in the crystallization process of a one-phase metal, if all grains start to grow simultaneously from these nucleation points at the same rate, microstructure produced will be in the form of a Voronoi diagram.…”
Section: Voronoi Finite-element Modelingmentioning
confidence: 99%
“…In VFEM, the strain energy method is used to extract the stiffness matrix for the triangular elements. For more detailed information about the VFEM, please refer to [33].…”
Section: Voronoi Finite-element Modelingmentioning
confidence: 99%
See 1 more Smart Citation